Discrimination Training with Multimodal Stimuli Changes Activity in the Mushroom Body of the Hawkmoth Manduca sexta - Balkenius, Anna; Hansson, Bill (PLOS ONE, 2012)
Background The mushroom bodies of the insect brain play an important role in olfactory processing, associative learning and memory. The mushroom bodies show odor-specific spatial patterns of activity and are also influenced by visual stimuli. Methodology/Principal Findings Functional imaging was used to investigate changes in the in vivo responses of the mushroom body of the hawkmoth Manduca sexta during multimodal discrimination training. A visual and an odour stimulus were presented either together or individually. Initially, mushroom body activation patterns were identical to the odour stimulus and the multimodal stimulus. After training, however, the mushroom body response to the rewarded multimodal stimulus was significantly lower than the response to the unrewarded unimodal odour stimulus, indicating that the coding of the stimuli had changed as a result of training. The opposite pattern was seen when only the unimodal odour stimulus was rewarded. In this case, the mushroom body was more strongly activated by the multimodal stimuli after training. When no stimuli were rewarded, the mushroom body activity decreased for both the multimodal and unimodal odour stimuli. There was no measurable response to the unimodal visual stimulus in any of the experiments. These results can be explained using a connectionist model where the mushroom body is assumed to be excited by olfactory stimulus components, and suppressed by multimodal configurations. Conclusions Discrimination training with multimodal stimuli consisting of visual and odour cues leads to stimulus specific changes in the in vivo responses of the mushroom body of the hawkmoth.